2010
DOI: 10.1177/0897190010366927
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Volunteer Pharmacy Preceptors

Abstract: The results of this national volunteer preceptor survey may assist pharmacy school leaders in understanding how location, practice type, and population density affect experiential education, preceptor time-quality issues, and site compensation so they can take necessary actions to improve quality of student practice experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…However, these data were not available, except for data regarding the gender distribution [20, 21]. Although, the number of respondents was much more than those in the nationwide preceptor survey of the United States or in the Korean KAPE survey, it is hard to eliminate the selection bias in this study, or to insist that these findings are likely to be similar across all students [2, 22]. Despite these limitations, this is the first study reporting a nationwide pharmacy student survey in Korea, and involved the largest number of students participating voluntarily from both metropolitan and provincial areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these data were not available, except for data regarding the gender distribution [20, 21]. Although, the number of respondents was much more than those in the nationwide preceptor survey of the United States or in the Korean KAPE survey, it is hard to eliminate the selection bias in this study, or to insist that these findings are likely to be similar across all students [2, 22]. Despite these limitations, this is the first study reporting a nationwide pharmacy student survey in Korea, and involved the largest number of students participating voluntarily from both metropolitan and provincial areas.…”
Section: Discussionmentioning
confidence: 99%
“…To identify factors affecting CPEPM outcome in students after practice, univariate analysis was performed, followed by multivariate linear regression analysis using statistically significant variables, in addition to the data regarding the gender and practice sites [22, 23]. CPEPM outcome was taken as a dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2011 survey administered at multiple hospitals, clinical staff identified electronic journals, PubMed, UpToDate, and electronic books-all online resources-as the most frequently consulted information resources used while providing patient care [3]. Access to online resources is also a highly valued incentive for preceptors who train students [4][5][6]. Many preceptors work at the hospitals affiliated with the academic institutions offering these clinical training programs.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the Doctor of Pharmacy curriculum requirements, preceptors spend a lot of time with student pharmacists. 3 Thus, preceptors can provide feedback on the knowledge and performance of students during clinical practice. Existing research has reported on the use of preceptors to provide the school with feedback on the perceived abilities of their graduates in several areas, including clinical skills, leadership, and pharmacy laws.…”
Section: Introductionmentioning
confidence: 99%